2012
DOI: 10.1016/s2212-4268(12)60006-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between growth of facial morphology and chronologic age in preschool children with obstructive sleep apnea

Abstract: Obstructive sleep apnea in children may be associated with growth disturbances of the nasal floor and corpus length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…From those studies included in this review, three studies dated back to 1999 23 , 24 , 25 and one study published in 2021. 26 Four studies were performed in a Chinese population, 16 , 17 , 26 , 27 three in Italy, 19 , 23 , 25 two in Brazil 20 , 28 and Japan 21 , 29 ; and one each in Sweden, 30 and Korea. 18 A majority of the studies had a cross-sectional study design 16 , 18 , 19 , 20 , 21 , 23 , 24 , 26 , 28 , 29 , 31 with the rest having a case-control 17 , 25 , 27 , 32 while one study had a cohort study design.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From those studies included in this review, three studies dated back to 1999 23 , 24 , 25 and one study published in 2021. 26 Four studies were performed in a Chinese population, 16 , 17 , 26 , 27 three in Italy, 19 , 23 , 25 two in Brazil 20 , 28 and Japan 21 , 29 ; and one each in Sweden, 30 and Korea. 18 A majority of the studies had a cross-sectional study design 16 , 18 , 19 , 20 , 21 , 23 , 24 , 26 , 28 , 29 , 31 with the rest having a case-control 17 , 25 , 27 , 32 while one study had a cohort study design.…”
Section: Resultsmentioning
confidence: 99%
“… 26 Four studies were performed in a Chinese population, 16 , 17 , 26 , 27 three in Italy, 19 , 23 , 25 two in Brazil 20 , 28 and Japan 21 , 29 ; and one each in Sweden, 30 and Korea. 18 A majority of the studies had a cross-sectional study design 16 , 18 , 19 , 20 , 21 , 23 , 24 , 26 , 28 , 29 , 31 with the rest having a case-control 17 , 25 , 27 , 32 while one study had a cohort study design. 30 The sample sizes for the OSA group ranged from 13 25 to 77 20 and the age from 4.5 years 25 to 12.6 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous literature found that orthodontists can accurately diagnose nasal breathing and advised collaboration between orthodontists and otolaryngologists regarding mouth breathing diagnosis [3]. Lymphoid tissue develops fast after birth, reaches its peak size in childhood, begins to regress around the age of 8-10 years, and usually entirely diminishes around 12-14 years [29]. Hence, in our study: the history taking and clinical tests were used as preliminary screening tests for detection of mouth breathing, and the otolaryngologists confirmed the diagnosis, cooperation between the two disciplines led to a better diagnosis and treatment planning [3].…”
Section: Discussionmentioning
confidence: 99%
“…Behlfelt et al [34] suspected that the lower HBP in mouth breathers was attributed to lower position of the tongue and to allow for more airway patency as the airway volume might be decreased in the mouth breathers [29], whereas, Chaves et al [33] suggested that the upward HBP is a compensatory mechanism; as mouth breathing is accompanied with clockwise rotation of the mandible, which might release the tension applied by suprahyoid muscle to hyoid bone, thus led to an inferior HBP and constricted pharynx as well, then mouth breathers tended to extend their heads to allow for more airway patency, this posture exaggerated the tension applied by suprahyoid muscle, which consequently pulled hyoid bone to a superior position. Moreover, in our study, we also used Sella point to determine HBP as it is a more stable reference point than cervical vertebrae and mandible [32].…”
Section: Discussionmentioning
confidence: 99%